Theoretical base in masters thesis from Institute of Public Health of National University of Colombia, 2000-2005 - Álvaro Franco; Gloria Molina; Gustavo A. Cabrera (Universidad de Antioquia, 2008)
Objective: to explore theories and theoretical models used in theses in master degrees at Public Health Institute, National University of Colombia. Methods: in June 2005 the central library of National University was visited for a trained reader to review theses on public health or infections-tropical health finished from January 2000 to May 2005. Results: fifty theses, 34 on public health and 16 on infections-tropical health were evaluated, which included an average of 22 pages of theoretical framework. Only 5 (10%) theses, 4 in public health and 1 in tropical health, used theoretical basis according to the criteria previously established. Conclusions: application of theoretical basis to direct the theme, methodology and analysis of reviewed degree theses, finished between 2000 and 2005 is lower than expected.